Modeling and in vivo experimental validation of 1,064 nm laser interstitial thermal therapy on brain tissue - Cao, Peng; Shi, Dingsheng; Li, Ding; Zhu, Zhoule; Zhu, Junming; Zhang, Jianmin; Bai, Ruiliang (Frontiers in Neurology, 2023)
Laser interstitial thermal therapy (LITT) at 1064 nm is widely used to treat epilepsy and brain tumors; however, no numerical model exists that can predict the ablation region with careful in vivo validation. In this study, we proposed a model with a system of finite element methods simulating heat transfer inside the brain tissue, radiative transfer from the applicator into the brain tissue, and a model for tissue damage. To speed up the computation for practical applications, we also validated P1-approximation as an efficient and fast method for calculating radiative transfer by comparing it with Monte Carlo simulation. Finally, we validated the proposed numerical model in vivo on six healthy canines and two human patients with epilepsy and found strong agreement between the predicted temperature profile and ablation area and the magnetic resonance imaging-measured results. Our results demonstrate the feasibility and reliability of the model in predicting the ablation area of 1064 nm LITT, which is important for presurgical planning when using LITT.